Security Index - Mojanoski T., Cane; GJurovski, Marjan (University “Ss. Kliment Ohridski”– Bitola Faculty of Security – Skopje Konrad-Adenauer-Stiftung, 2018)
This research is a product of the established cooperation between the Faculty of Security Studies, Skopje and the Macedonia Office of the Konrad Adenauer Stiftung. To compile a Security Index was a challenge for the team of authors to devise a comprehensive tool that comprises a significant number of indicators which can encourage to draw conclusions, do define policies, or to undertake specific actions in the sphere of security. The index is designed as an extra tool for creating security policies, for early warning and for initiating organized and, if allowed or required, joint and coordinated actions of the responsible institutions to eliminate challenges, risks or security threats. Drafting the Security Index, in the preliminary phase, revealed quite some issues and dilemmas. By and large, they can be grouped as follows: а) questions related to theoretical and conceptual differences in the perception of security and difficulties in determining the concept, structure and framework of the term; б) issues related to the methodological approach, especially regarding analytical and research procedures that influence the objectivity and determine the content of the Index; в) data choices, their openness, availability, reliability and usability. That is why the team defined the following goals: а) to carry out pilot research that will offer a possible approach and response to the question of defining the term security; б) to provide an indicator framework, based on which data will be collected using quantitative and qualitative research design, and 12 в) to encourage activities to improve material resources and staff capacity, that is, to create an optimal time frame for permanently updating the index by improving the organizational (by including other experts and researchers) and material basis (by encouraging and organizing publicly available data bases, procuring software and training staff). The content of this edition is an initial product and preliminary concept, offering certain knowledge and revealing some questions and dilemmas, not only due to the space, but also to the time available to the team. We expect that by the end of 2018, after completion of the second preliminary phase, when qualitative instruments for collecting data will be applied, the research topic, the indicator framework and the structure of the Index will be more clearly and comprehensively defined. The research team expects to receive comments, assessments and ideas for compiling the Security Index, which it will treat with special attention. We will try to extract the optimal solutions for creating a research tool to measure the level of security in the Republic of Macedonia, which will serve for initiating complex security activities that involve the identification, prevention and resolution of security problems, and for providing assumptions for the comparison and ranking of the security institutions, as well as between different states. The Security Index is hence a tool for synthesizing the complex phenomenon of security, the debate on which we hope to make a small contribution to. Finally, we would like to express our sincere gratitude to Mr. Johannes Rey, Head of the Konrad Adenauer Stiftung`s Macedonia Office, and to his associates for their continuing support. We would also like to thank the Dean‘s Administration Security Index 13 at the Faculty of Security Studies, Skopje, and the reviewers, Prof. Dr. Tome Batkovski from the Faculty of Security Studies–, and Prof. Dr. Nedžad Korajlić from the Faculty of Criminal Justice, Criminology and Security Studies at the University of Sarajevo.